"Voices of Fear and Safety" Women's ambivalence towards breast cancer and breast health: a qualitative study from Jordan - Taha Hana; Al-Qutob Raeda; Nyström Lennarth; Wahlström Rolf; Berggren Vanja (BMC, 2012)
Abstract Background Breast cancer is the leading cause of cancer mortality among Jordanian women. Breast malignancies are detected at late stages as a result of deferred breast health-seeking behaviour. The aim of this study was to explore Jordanian women's views and perceptions about breast cancer and breast health. Methods We performed an explorative qualitative study with purposive sampling. Ten focus groups were conducted consisting of 64 women (aged 20 to 65 years) with no previous history and no symptoms of breast cancer from four governorates in Jordan. The transcribed data was analysed using latent content analysis. Results Three themes were constructed from the group discussions: a) Ambivalence in prioritizing own health; b) Feeling fear of breast cancer; and c) Feeling safe from breast cancer. The first theme was seen in women's prioritizing children and family needs and in their experiencing family and social support towards seeking breast health care. The second theme was building on women's perception of breast cancer as an incurable disease associated with suffering and death, their fear of the risk of diminished femininity, husband's rejection and social stigmatization, adding to their apprehensions about breast health examinations. The third theme emerged from the women's perceiving themselves as not being in the risk zone for breast cancer and in their accepting breast cancer as a test from God. In contrast, women also experienced comfort in acquiring breast health knowledge that soothed their fears and motivated them to seek early detection examinations. Conclusions Women's ambivalence in prioritizing their own health and feelings of fear and safety could be better addressed by designing breast health interventions that emphasize the good prognosis for breast cancer when detected early, involve breast cancer survivors in breast health awareness campaigns and catalyse family support to encourage women to seek breast health care.